A magnetic ternary photocatalyst and its preparation method and application

By preparing the magnetic ternary photocatalyst AgBr/BiOBr/Fe3O4 and applying PMS to its surface, photocatalytic degradation is solved by using natural light, the existing photocatalytic degradation efficiency is limited and unrecyclable, and efficient and stable degradation of CBZ in water bodies and recycling of materials is achieved.

CN117138806BActive Publication Date: 2025-04-18FUZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311100631.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-29
Publication Date
2025-04-18
Estimated Expiration
2043-08-29

AI Technical Summary

Technical Problem

The existing photocatalysts have limited catalytic degradation efficiency and cannot be recovered and utilized, making it difficult to efficiently and stably degrade carbamazepine (CBZ) and its metabolites in water bodies.

Method used

The preparation method of the magnetic ternary photocatalyst AgBr/BiOBr/Fe3O4 is adopted. By combining Fe3O4 magnetic particles with AgBr and BiOBr, a composite material with high catalytic activity and easy recovery is formed, and monosulfate (PMS) is added to its surface as an activated substance, and photocatalytic degradation is performed using natural light.

Benefits of technology

The separation ability and photocatalytic activity of photogenerated carriers are significantly improved, and the efficient and stable degradation of CBZ in the water environment is achieved. By introducing magnetic particles Fe3O4, the problem of difficult recycling of traditional photocatalysts is solved, and the recycling ability is good.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117138806B_ABST
    Figure CN117138806B_ABST
Patent Text Reader

Abstract

The invention discloses a magnetic ternary photocatalyst and its preparation method and application. The preparation method comprises the following steps: preparing Fe3O4 magnetic particles; dissolving Bi(NO3)3·5H2O in ethylene glycol, then adding AgNO3 solution thereto, stirring and reacting in the dark to obtain a mixed solution; adding Fe3O4 magnetic particles to the mixed solution, stirring fully, then dropping KBr solution into the mixed system, placing it in a water bath for stirring and aging, then collecting the precipitate and washing and drying it to obtain AgBr / BiOBr / Fe3O4 magnetic ternary photocatalyst. The catalyst can effectively solve the problems of limited catalytic degradation efficiency and inability to recycle existing photocatalysts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water treatment, and in particular relates to a magnetic ternary photocatalyst and a preparation method and application thereof. Background Art

[0002] Pharmaceutically active compounds (PhACs) are commonly used to prevent and treat diseases in humans and animals. In recent years, the production and use of PhACs have continued to increase, exacerbating the risks to aquatic ecological environments. As a typical PhAC, carbamazepine (CBZ) is widely used to treat diseases such as epilepsy, manic depression, and trigeminal neuralgia, and has become one of the most commonly detected drugs in surface water and groundwater. The bioaccumulation and biomagnification of CBZ can lead to deterioration of embryonic development and disorders of the reproductive and nervous systems. Despite this, traditional wastewater treatment technologies cannot effectively treat CBZ and its metabolites because CBZ is difficult to biodegrade. Therefore, it is of great significance to find a method to efficiently degrade CBZ in water bodies.

[0003] The combination of photocatalytic technology and peroxymonosulfate (PMS)-based advanced oxidation technology (SR-AOPs) is a new coupling technology. The photocatalytic activation of peroxymonosulfate technology can solve problems such as the limited visible light response of photocatalysts, the easy recombination of electron holes in photocatalysts, the limited activation of peroxymonosulfate oxidants, and secondary pollution. This technology is not only conducive to promoting the separation efficiency of photogenerated carriers of semiconductor photocatalytic materials, but also can accelerate the activation of peroxymonosulfate to produce more active substances. The two work together to achieve the purpose of efficient degradation of PhACs.

[0004] Solar light-driven semiconductor photocatalysts have attracted much attention due to their suitable redox potential, environmental protection, sustainability and high efficiency. BiOBr has been widely used in the field of photocatalysis due to its good visible light response ability and special two-dimensional layered structure. However, single-component semiconductors usually undergo rapid recombination of photogenerated carriers, resulting in low quantum efficiency, and photocatalysts are difficult to separate, recycle, reuse, and further improve their activity, which limits their application. Therefore, it is urgent to invent a photocatalyst with strong catalytic performance and easy recycling and reuse to achieve efficient and stable degradation of CBZ. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides a magnetic ternary photocatalyst, a preparation method and application thereof, which can effectively solve the problems of limited catalytic degradation efficiency and non-recyclability of existing photocatalysts.

[0006] To achieve the above purpose, the technical solution adopted by the present invention to solve the technical problem is:

[0007] A method for preparing a magnetic ternary photocatalyst comprises the following steps:

[0008] (1) Preparation of Fe3O4 magnetic particles;

[0009] (2) dissolving Bi(NO3)3·5H2O in ethylene glycol, then adding AgNO3 solution thereto, stirring and reacting in the dark to prepare a mixed solution;

[0010] (3) Add the Fe3O4 magnetic particles in step (1) to the mixed solution in step (2), stir thoroughly, then drop the KBr solution into the mixed system, place it in a water bath for stirring and aging, then collect the precipitate and wash and dry it to obtain the AgBr / BiOBr / Fe3O4 magnetic ternary photocatalyst.

[0011] Furthermore, the concentration of Bi(NO3)3·5H2O in the mixed solution is 15-25 g / L, and the concentration of AgNO3 in the mixed solution is 0.5-2 g / L.

[0012] Furthermore, in step (3), the concentration of Fe3O4 magnetic particles in the mixed solution is 2-15wt%, and the concentration of KBr in the mixed system is 5-10g / L.

[0013] Furthermore, in step (3), the water bath temperature is 80-100° C., and the stirring aging time is 1-3 h.

[0014] A magnetic ternary photocatalyst is prepared by adopting the above preparation method.

[0015] The application of the above magnetic ternary photocatalyst in catalytic degradation of carbamazepine in water.

[0016] Furthermore, the specific operation method includes the following steps:

[0017] (1) adding a magnetic photocatalyst and peroxymonosulfate to a water body containing carbamazepine, and adjusting the pH of the solution to 3-9;

[0018] (2) The mixed solution is placed under natural light for photocatalytic degradation.

[0019] Furthermore, the concentration of permonosulfate in the water in step (1) is 0.4-1.0 mM, and the concentration of the magnetic photocatalyst is 0.2-0.5 g / L.

[0020] Furthermore, the peroxymonosulfate is potassium hydrogen persulfate.

[0021] Furthermore, the photocatalytic degradation time is 1-30 min.

[0022] The beneficial effects produced by the present invention are:

[0023] (1) The construction of the AgBr / BiOBr / Fe3O4 ternary photocatalyst in the present invention is conducive to reducing the interfacial charge resistance, which can effectively improve the separation ability of photogenerated carriers and enhance the visible light catalytic activity of the photocatalyst. At the same time, the addition of PMS as a photocatalytic activating substance can produce a large amount of active substances, which can synergistically achieve efficient and stable degradation of CBZ in the water environment.

[0024] (2) The AgBr / BiOBr / Fe3O4 ternary photocatalyst of the present invention introduces low-cost, highly stable and environmentally friendly magnetic particles Fe3O4, which enables the photocatalytic material to be quickly separated from the reaction medium under the action of an external magnetic field and has good recycling ability, thus solving the problem that traditional photocatalysts are difficult to recycle and reuse. The recyclable feature reduces the economic cost to a certain extent.

[0025] (3) The AgBr / BiOBr / Fe3O4 ternary photocatalyst of the present invention has a high response ability to visible light, and has more advantages in practical application compared to traditional photocatalysts that require ultraviolet light. In addition, PMS as an activating substance is inexpensive and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 XRD patterns of AgBr, BiOBr, AgBr / BiOBr, Fe3O4 and ABF-x (x=2, 5, 10 and 15) photocatalysts;

[0027] Figure 2 SEM images of AgBr, BiOBr, Fe3O4, AgBr / BiOBr and ABF-5 photocatalysts;

[0028] Figure 3 Infrared spectra of AgBr, BiOBr, Fe3O4, AgBr / BiOBr and ABF-5 photocatalysts;

[0029] Figure 4 This is the XPS spectrum analysis diagram of ABF-5 photocatalyst;

[0030] Figure 5 UV-vis graphs and band gap diagrams of AgBr, BiOBr, Fe3O4, AgBr / BiOBr and ABF-5 photocatalysts;

[0031] Figure 6 The room temperature hysteresis loop diagram of Fe3O4 and ABF-5 magnetic photocatalysts;

[0032] Figure 7 This is a statistical diagram of the effect of visible light photocatalytic activation of PMS and degradation of CBZ by the magnetic composite material ABF at different Fe3O4 doping amounts;

[0033] Figure 8 It is a statistical diagram of the effect of different dosages of PMS on the degradation of CBZ by visible light catalytic activation of PMS in magnetic composite material ABF-5;

[0034] Fig. 9 It is a statistical diagram of the effect of different pH values ​​on the visible light photocatalytic activation of PMS and degradation of CBZ by magnetic composite material ABF-5;

[0035] Fig.10 This is a statistical diagram of the recycling experiment effect of magnetic ABF-5 photocatalyst for CBZ degradation;

[0036] Fig.11 This is a statistical chart of the removal effect of different photocatalysts on CBZ under visible light (Vis) system, PMS system and Vis / PMS system. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, rather than all of the embodiments.

[0038] Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present invention.

[0039] It should be noted that relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.

[0040] The features and performance of the present invention are further described in detail below in conjunction with the embodiments and drawings.

[0041] Example 1

[0042] A magnetic ternary photocatalyst, the preparation method of which comprises the following steps:

[0043] (1) 1.2 g (4.4 mmol) of FeCl3·6H2O was dissolved in 75 mL of ethylene glycol (EG) by ultrasonication to form a transparent solution. Subsequently, 3.60 g (44.0 mmol) of NaAc was added during stirring and stirred vigorously for 0.5 h to obtain a clear dark yellow solution.

[0044] (2) The dark yellow solution obtained in step (1) was transferred to a 90 mL Teflon-lined stainless steel autoclave and maintained at 200° C. for 16 h. After cooling to room temperature, the black product was cross-washed three times with ethanol and water, and then placed in a 60° C. oven to dry for 12 h. Finally, it was ground to obtain Fe3O4 magnetic particles;

[0045] (3) Add 1.456 g Bi(NO3)3·5H2O to 45 mL EG and dissolve it by ultrasonication to make it uniformly dispersed. Then, pour in 25 mL ultrapure water containing 0.063 g AgNO3 and stir in the dark for 0.5 h.

[0046] (4) 0.0143 g of the Fe3O4 magnetic particles obtained in step (2) was added to the solution obtained in step (3), and the mixture was stirred for 30 min using a mechanical stirrer. Then, 25 mL of KBr (0.714 g) aqueous solution was slowly added dropwise to the solution, and the solution was placed in a 90°C water bath and aged for 2 h with magnetic stirring;

[0047] (5) The gray precipitate obtained in step (4) was cooled to room temperature, washed alternately with ethanol and deionized water several times to wash away excess materials and EG solution residues, and then dried at 60 °C for 12 h to obtain a magnetic ternary photocatalyst, labeled as ABF-2.

[0048] Example 2

[0049] A magnetic ternary photocatalyst, the preparation method of which comprises the following steps:

[0050] (1) 1.2 g (4.4 mmol) of FeCl3·6H2O was dissolved in 75 mL of ethylene glycol (EG) by ultrasonication to form a transparent solution. Subsequently, 3.60 g (44.0 mmol) of NaAc was added during stirring and stirred vigorously for 0.5 h to obtain a clear dark yellow solution.

[0051] (2) The dark yellow solution obtained in step (1) was transferred to a 90 mL Teflon-lined stainless steel autoclave and maintained at 200° C. for 16 h. After cooling to room temperature, the black product was cross-washed three times with ethanol and water, and then placed in a 60° C. oven to dry for 12 h. Finally, it was ground to obtain Fe3O4 magnetic particles;

[0052] (3) Add 1.74 g Bi(NO3)3·5H2O to 45 mL EG and dissolve it by ultrasonication to make it uniformly dispersed. Then, pour in 25 mL ultrapure water containing 0.14 g AgNO3 and stir in the dark for 0.5 h.

[0053] (4) 0.0368 g of the Fe3O4 magnetic particles obtained in step (2) was added to the solution obtained in step (3), and the mixture was stirred for 30 min using a mechanical stirrer. Then, 25 mL of KBr (0.95 g) aqueous solution was slowly added dropwise to the solution, and the solution was placed in a 90°C water bath and aged for 2 h with magnetic stirring;

[0054] (5) The gray precipitate obtained in step (4) was cooled to room temperature, washed alternately with ethanol and deionized water several times to wash away excess materials and EG solution residues, and then dried at 60°C for 12 h to obtain a magnetic ternary photocatalyst, labeled as ABF-5.

[0055] Example 3

[0056] A magnetic ternary photocatalyst, the preparation method of which comprises the following steps:

[0057] (1) 1.2 g (4.4 mmol) of FeCl3·6H2O was dissolved in 75 mL of ethylene glycol (EG) by ultrasonication to form a transparent solution. Subsequently, 3.60 g (44.0 mmol) of NaAc was added during stirring and stirred vigorously for 0.5 h to obtain a clear dark yellow solution.

[0058] (2) The dark yellow solution obtained in step (1) was transferred to a 90 mL Teflon-lined stainless steel autoclave and maintained at 200° C. for 16 h. After cooling to room temperature, the black product was cross-washed three times with ethanol and water, and then placed in a 60° C. oven to dry for 12 h. Finally, it was ground to obtain Fe3O4 magnetic particles;

[0059] (3) Add 1.05 g Bi(NO3)3·5H2O to 45 mL EG and dissolve it by ultrasonication to make it uniformly dispersed. Then, pour in 25 mL ultrapure water containing 0.035 g AgNO3 and stir in the dark for 0.5 h.

[0060] (4) 0.0780 g of the Fe3O4 magnetic particles obtained in step (2) was added to the solution obtained in step (3), and the mixture was stirred for 30 min using a mechanical stirrer. Then, 25 mL of KBr (0.475 g) aqueous solution was slowly added dropwise to the solution, and the solution was placed in a 90°C water bath and aged for 2 h with magnetic stirring;

[0061] (5) The gray precipitate obtained in step (4) was cooled to room temperature, washed alternately with ethanol and deionized water several times to wash away excess materials and EG solution residues, and then dried at 60°C for 12 h to obtain a magnetic ternary photocatalyst, labeled as ABF-10.

[0062] Example 4

[0063] A magnetic ternary photocatalyst, the preparation method of which comprises the following steps:

[0064] (1) 1.2 g (4.4 mmol) of FeCl3·6H2O was dissolved in 75 mL of ethylene glycol (EG) by ultrasonication to form a transparent solution. Subsequently, 3.60 g (44.0 mmol) of NaAc was added during stirring and stirred vigorously for 0.5 h to obtain a clear dark yellow solution.

[0065] (2) The dark yellow solution obtained in step (1) was transferred to a 90 mL Teflon-lined stainless steel autoclave and maintained at 200° C. for 16 h. After cooling to room temperature, the black product was cross-washed three times with ethanol and water, and then placed in a 60° C. oven to dry for 12 h. Finally, it was ground to obtain Fe3O4 magnetic particles;

[0066] (3) Add 1.542 g Bi(NO3)3·5H2O to 45 mL EG and dissolve it by ultrasonication to make it uniformly dispersed. Then, pour in 25 mL ultrapure water containing 0.105 g AgNO3 and stir in the dark for 0.5 h.

[0067] (4) 0.1235 g of the Fe3O4 magnetic particles obtained in step (2) was added to the solution obtained in step (3), and the mixture was stirred for 30 min using a mechanical stirrer. Then, 25 mL of KBr (0.76 g) aqueous solution was slowly added dropwise to the solution, and the solution was placed in a 90°C water bath and aged for 2 h with magnetic stirring.

[0068] (5) The gray precipitate obtained in step (4) was cooled to room temperature, washed with ethanol and deionized water alternately several times to wash away excess materials and EG solution residues, and then dried at 60°C for 12 h to obtain a magnetic ternary photocatalyst, labeled as ABF-15.

[0069] Experimental example

[0070] 1. Taking the magnetic ternary photocatalyst prepared in Example 1 as an example, the crystal phase, micromorphology, surface functional groups, chemical composition, optical properties and magnetic properties of the magnetic ternary photocatalyst were tested. The specific test results are shown in Figure 1-6 .

[0071] Figure 1 a is the XRD pattern of AgBr, BiOBr, and AgBr / BiOBr. Figure 1 b is the XRD pattern of Fe3O4 and ABF-x (x = 2, 5, 10 and 15) photocatalysts; Figure 1 a It can be seen that the diffraction peaks of the original BiOBr and AgBr are narrow and sharp, indicating that the prepared single-component material has good crystallinity and high purity. When AgBr is combined with BiOBr, the original AgBr diffraction peak can be identified in the diffraction pattern of the AgBr / BiOBr binary photocatalyst, indicating the successful incorporation of AgBr. Figure 1 b It can be seen that the prepared Fe3O4 magnetic particles do not have the characteristic peaks of other substances, indicating that Fe3O4 with good crystallinity has been successfully prepared. For the magnetic ABF composite photocatalyst, the original Fe3O4 crystal plane (311) and crystal plane (440) both exist in the XRD spectrum of ABF, the main diffraction peaks of AgBr / BiOBr can also be found in the ABF diffraction spectrum, and the characteristic peaks of BiOBr and AgBr are retained in the ABF composite catalyst, indicating that the ABF composite photocatalyst has been successfully prepared.

[0072] Figure 2 SEM images of AgBr, BiOBr, Fe3O4, AgBr / BiOBr and ABF-5 photocatalysts, where a is AgBr, b is BiOBr, c is Fe3O4, d is AgBr / BiOBr, and e is ABF-5; Figure 2 a shows that the synthesized AgBr catalyst has a distinct crystal morphology, with crystals of different sizes and smooth surfaces; Figure 2 b shows that the BiOBr surface is smooth and has an irregular flake structure; Figure 2 c shows that Fe3O4 is an aggregated spherical particle with a slightly rough surface and relatively uniform size; Figure 2 d shows that in the AgBr / BiOBr binary composite material, AgBr and BiOBr can form a close contact, which to some extent explains the existence of a certain interaction force between AgBr and BiOBr; Figure 2e shows that the Fe3O4 magnetic beads are evenly distributed on the surface of the AgBr / BiOBr binary composite matrix, which can play a certain role in the electron transport inside the magnetic ABF-5 composite catalyst. Overall, SEM characterization shows that there is a close contact between Fe3O4 and AgBr / BiOBr, which is conducive to the exposure of the active sites of the magnetic composite material ABF-5 and can increase the catalytic efficiency.

[0073] Figure 3 The infrared spectra of AgBr, BiOBr, Fe3O4, AgBr / BiOBr and ABF-5 photocatalysts at different wave numbers are shown. It can be seen that for AgBr / BiOBr, the characteristic peak of the original BiOBr is observed in the infrared spectrum of the AgBr / BiOBr binary photocatalyst and the absorption peak belonging to the Bi-O bond is slightly red-shifted, which indicates that the AgBr / BiOBr photocatalyst is successfully synthesized and there is a strong interaction. In the infrared spectrum of ABF-5, the absorption peak of the Fe-O bond is observed to be blue-shifted and the peak of Bi-O is red-shifted, which indicates that there is a significant interaction between the components in the magnetic composite material ABF-5. The above analysis further proves the successful synthesis of the magnetic composite material ABF-5.

[0074] Figure 4 The XPS spectrum analysis diagram of the magnetic ABF-5 photocatalyst, where a is C1s, b is Ag 3d, c is Bi 4f, d is Fe 2p, e is Br 3d and f is O1s; Figure 4 In a, there are two characteristic peaks at 284.80 eV and 286.33 eV in the C 1s spectrum, which are attributed to the inevitable external carbon source during the instrument test process (corresponding to the C=C bond and the CO bond, respectively); Figure 4 The spectrum of Ag 3d is shown in b, and the characteristic peaks at 367.87 eV and 373.86 eV are matched to Ag + Ag 3d 5 / 2 and Ag 3d 3 / 2 track Figure 4 In c, the Bi 4f fitting of the ABF-5 composite material shows significant characteristic peaks with binding energies of 159.38 eV and 164.68 eV, which are matched to Bi 3+ Bi 4f 7 / 2 and Bi 4f 5 / 2 track; Figure 4 d shows that the Fe 2p spectrum of ABF-5 is split into five characteristic peaks. The characteristic peaks at 710.28 eV and 723.33 eV are attributed to Fe 2+ Fe 2p 3 / 2 and Fe 2p 1 / 2orbital, while the characteristic peaks at 711.51eV and 725.94eV may be related to Fe 3+ Fe 2p 3 / 2 and Fe 2p 1 / 2 Orbital related. 2+ with Fe 3+ The occupancy ratio is 1:1.9, which is close to the theoretical value of Fe3O4 (Fe 2+ :Fe 3+ =1:2). In addition, the satellite peak at 715.81 eV shows that Fe 2+ and Fe 3+ , indicating that the successful incorporation of Fe3O4 and the change in valence state are more conducive to the activation of PMS on the surface of ABF-5 to cause electron transfer reaction; for the Br 3d spectrum, Figure 4 e shows that ABF-5 corresponds to sharp peaks at 68.43eV and 69.46eV, which are Br3d 5 / 2 and Br 3d 3 / 2 track Figure 4 In the O1s spectrum of ABF-5, there are three characteristic peaks at 530.22 eV, 530.72 eV and 532.66 eV, corresponding to the lattice oxygen O 2- The interactions between the chemical bonds in ABF-5 further confirmed the successful construction of the magnetic composite material ABF-5.

[0075] Figure 5 The UV-vis graphs and band gap graphs of AgBr, BiOBr, Fe3O4, AgBr / BiOBr and ABF-5 photocatalysts, where a is the UV-vis graph and b is the band gap graph; Figure 5 It can be seen that the light absorption band edges of AgBr and BiOBr are located at about 508nm and 440nm, respectively, and both can produce a certain degree of light response ability in the visible light region. The light absorption edge of AgBr / BiOBr is located between AgBr and BiOBr, and its optical properties are improved. The introduction of Fe3O4 to modify the AgBr / BiOBr binary photocatalytic material increases the light absorption band edge of ABF-5 slightly, and it shows visible light response ability around 492nm. This is due to the strong light capture characteristics of Fe3O4 in the whole band. The magnetic ABF-5 composite material not only improves the absorption capacity in the visible light region, but also broadens the visible light response range. Figure 5b shows the band gap energy results of magnetic photocatalysts. The band gap energies of AgBr, BiOBr, AgBr / BiOBr and ABF-5 are 2.55 eV, 2.92 eV, 2.90 eV and 2.88 eV, respectively, which indicates that the introduction of AgBr and Fe3O4 effectively reduces the band gap of AgBr / BiOBr and ABF-5, thereby improving the photocatalytic activity of the composite materials.

[0076] Figure 6 The room temperature hysteresis loop statistics of Fe3O4 and ABF-5 magnetic photocatalysts, where the inset in the upper left corner shows the state of the ABF-5 photocatalyst being attracted by the external magnetic field; it can be seen that both the Fe3O4 magnetic particles and the magnetic composite material ABF-5 have significant hysteresis loops and are in the form of smooth S-shaped curves. Compared with the Fe3O4 magnetic particles, the saturation magnetic induction intensity of the magnetic composite material ABF-5 is reduced, which may be due to the large proportion of non-magnetic components AgBr and BiOBr in the magnetic composite material ABF-5 and the relatively low proportion of magnetic Fe3O4 particles. The inset in the lower right corner of the figure shows that both the magnetic Fe3O4 particles and the magnetic composite material ABF-5 have hysteresis phenomena, and the corresponding high coercive forces are 0.04KOe and 0.09KOe, respectively. It can be observed from the illustration in the upper left corner of the figure that the magnetic composite material ABF-5 can be evenly distributed in water without being disturbed by the magnetic field, but is quickly adsorbed to the glass wall on the strong magnetic side and aggregated after being acted upon by an external magnetic field. It can be inferred that the magnetic composite material ABF-5 can achieve rapid separation and recovery of photocatalysts under the condition of an external magnetic field.

[0077] 2. Prepare 10mg / L CBZ solution, then measure 4 portions of 100mL CBZ solution into 150mL quartz beakers, then add 0.3g / L ABF-2, ABF-5, ABF-10 and ABF-15 into the quartz beakers, ultrasonicate the quartz beakers for 30s and put them into the photocatalytic reaction device (the reaction device is equipped with a mechanical stirrer, a 500W xenon lamp, a UV cutoff filter (λ>400nm) and a cooling water circulation system. When in use, turn on the cooling water circulation system to keep the temperature in the photocatalytic box at 25°C). Stir thoroughly for 30min with a mechanical stirrer in a dark state to ensure that the magnetic photocatalyst and CBZ molecules reach a dark adsorption saturation state. This operation is a dark adsorption-analysis experiment. Then add 0.6mM PMS to the reaction solution, the initial pH value of the solution is 4.53, and turn on the xenon lamp (simulating natural light) to carry out the photocatalytic activation experiment. During the process of PMS degradation by magnetic photocatalytic material activation, 2 mL of water samples were collected at 0, 2, 5, 10, 15, and 30 min using a pipette, and the photocatalytic material and impurities were filtered through a 0.22 μm membrane filter. The samples were then injected into a liquid vial containing 50 μL of ascorbic acid (1 mol / L). After being mixed evenly with a small oscillator, the CBZ concentration was detected by HPLC to analyze the degradation effect. Three parallel experiments were performed each time, and the specific results are shown in Figure 7 . Figure 7 The experimental results show that the degradation rate of CBZ increases first and then decreases with the increase of Fe3O4 dosage. When the Fe3O4 dosage increases from 2wt.% to 5wt.%, the CBZ degradation rate increases, which indicates that within a certain range, the increase of Fe3O4 dosage can accelerate the Fe(II) / Fe(III) redox activation of PMS; when the Fe3O4 dosage further increases to 10wt.% and 15wt.%, the CBZ degradation rate decreases. This is because the excess Fe3O4 shields the photocatalytic active sites of BiOBr and AgBr, promotes the recombination of photogenerated carriers, and reduces the ability to activate PMS, resulting in a decrease in catalytic efficiency. Therefore, ABF-5 (Fe3O4 dosage of 5wt.%) is the optimal magnetic composite material. At this time, the photocatalyst material has the best adsorption and degradation effect on CBZ.

[0078] 3. Prepare 10 mg / L CBZ solution, measure 100 mL CBZ solution into 150 mL quartz beakers respectively, then add 0.3 g / L ABF-5 in Example 2 into the quartz beaker, then ultrasonicate the quartz beaker for 30 seconds and put it into a photocatalytic reaction device (the reaction device is equipped with a mechanical stirrer, a 500 W xenon lamp, an ultraviolet cutoff filter (λ>400 nm) and a cooling water circulation system. When in use, turn on the cooling water circulation system to keep the temperature in the photocatalytic box at 25°C), stir thoroughly for 30 minutes with a mechanical stirrer in a light-proof state to ensure that the magnetic photocatalyst and the CBZ molecules reach a dark adsorption saturation state. This operation is a dark adsorption-analysis experiment; then add 0.4 mM, 0.6 mM, 0.8 mM and 1.0 mM PMS into the reaction solution respectively, the initial pH value of the solution is 4.53, and turn on the xenon lamp for a photocatalytic activation experiment. During the process of PMS degradation by magnetic photocatalytic material activation, 2 mL of water samples were collected at 0, 2, 5, 10, 15, and 30 min using a pipette, and the photocatalytic material and impurities were filtered through a 0.22 μm membrane filter. The samples were then injected into a liquid vial containing 50 μL of ascorbic acid (1 mol / L). After being mixed evenly with a small oscillator, the CBZ concentration was detected by HPLC to analyze the degradation effect. Three parallel experiments were performed each time, and the specific results are shown in Figure 8 The experimental results show that when the PMS concentration increases from 0.4mM to 0.6mM, the degradation efficiency of CBZ increases accordingly. This is mainly because the appropriate PMS dosage can capture photogenerated electrons and inhibit the recombination of photogenerated carriers in the photocatalyst, thereby obtaining more electrons and holes to participate in the reaction to generate active substances to promote the degradation of CBZ; however, when the PMS dosage is further increased to 0.8mM and 1.0mM, the degradation rate of CBZ gradually decreases. This is because the excess PMS has a self-quenching effect and generates ·HO2 and ·SO5 with low oxidation ability. - In addition, the photogenerated electrons produced by the photocatalyst may not be enough to activate the excess PMS in the ABF-5 / Vis / PMS system, thus forming a light energy competition. Therefore, the optimal PMS dosage is 0.6mM. When the PMS dosage is 0.6mM, the adsorption and degradation effect of CBZ is the best.

[0079] Fourth, prepare 10 mg / L CBZ solution, measure 100 mL CBZ solution in 150 mL quartz beakers, then add 0.3 g / L ABF-5 in Example 2 to the quartz beaker, then ultrasonicate the quartz beaker for 30 seconds and put it into a photocatalytic reaction device (the reaction device is equipped with a mechanical stirrer, a 500 W xenon lamp, an ultraviolet cutoff filter (λ> 400 nm) and a cooling water circulation system. When in use, turn on the cooling water circulation system to keep the temperature in the photocatalytic box at 25 ° C). Stir thoroughly for 30 minutes with a mechanical stirrer in a light-proof state to ensure that the magnetic photocatalyst and the CBZ molecules reach a dark adsorption saturation state. This operation is a dark adsorption-analysis experiment; then add 0.6 mM PMS to the reaction solution, adjust the initial pH of the solution to 3, 5, 7, 9, 11 and 4.53 (unadjusted value) with 0.1 M H2SO4 and 0.1 M NaOH, respectively, and turn on the xenon lamp for a photocatalytic activation experiment. During the process of PMS degradation by magnetic photocatalytic material activation, 2 mL of water samples were collected at 0, 2, 5, 10, 15, and 30 min using a pipette, and the photocatalytic material and impurities were filtered through a 0.22 μm membrane filter. The samples were then injected into a liquid vial containing 50 μL of ascorbic acid (1 mol / L). After being mixed evenly with a small oscillator, the CBZ concentration was detected by HPLC to analyze the degradation effect. Three parallel experiments were performed each time, and the specific results are shown in Fig. 9 The experimental results showed that the optimal initial pH value was 4.53.

[0080] 5. Prepare 10mg / L CBZ solution, measure 100mL CBZ solution in a 150mL quartz beaker, then add 0.3g / L ABF-5 in Example 2 to the quartz beaker, then ultrasonicate the quartz beaker for 30s and put it into a photocatalytic reaction device (the reaction device is equipped with a mechanical stirrer, a 500W xenon lamp, an ultraviolet cutoff filter (λ>400nm) and a cooling water circulation system. When in use, turn on the cooling water circulation system to keep the temperature in the photocatalytic box at 25°C), and stir thoroughly for 30min with a mechanical stirrer in a light-proof state to ensure that the magnetic photocatalyst and the CBZ molecules reach a dark adsorption saturation state. This operation is a dark adsorption-analysis experiment. Then add 0.6mM PMS to the reaction solution, the initial pH of the solution is 4.53, and turn on the xenon lamp for a photocatalytic activation experiment. After each CBZ degradation experiment, a soft magnet was used to separate the magnetic photocatalyst and the reaction solution, and the photocatalyst was washed several times with pure water and anhydrous ethanol. After the photocatalyst was dried, it was used in a new experimental solution for operation cycles. The cycle experiment of magnetic photocatalyst activation of PMS to remove CBZ was carried out 5 times, and the specific results are shown in Fig.10The experimental results show that the magnetic ABF-5 photocatalyst is easily separated by an external magnet and is a recyclable, stable and durable photocatalyst. After being recycled five times, the photocatalyst still has a good degradation effect on CBZ in the solution.

[0081] 6. Fe3O4, BiOBr, AgBr, AgBr / BiOBr and magnetic composite material ABF-5 were placed in visible light (Vis) system, PMS system and Vis / PMS system respectively to conduct CBZ removal experiment in the solution. The CBZ concentration in the solution was controlled to be 10 mg / L, the pH value of the solution was 4.53, and the concentration of the added material was 0.3 g / L. In the Vis system, only the xenon lamp (visible light) was turned on, and PMS was not added to conduct the degradation experiment; in the PMS system, only 0.6 mM PMS was added, and the xenon lamp (visible light) was not turned on, and the degradation experiment was carried out under light-proof conditions; in the Vis / PMS system, 0.6 mM PMS was added, and the xenon lamp (visible light) was turned on for degradation experiments; three parallel experiments were conducted each time, and the specific results are shown in Fig.11 .

[0082] Fig.11 a is a statistical diagram of the degradation results of various materials under the Vis system. It can be seen that under the Vis system, the degradation effect of AgBr / BiOBr on CBZ is better than that of ABF-5 material;

[0083] Fig.11 b is the statistical diagram of the degradation results of each material under the PMS system. It can be seen that under the PMS system, the ABF-5 material has the best degradation effect on CBZ;

[0084] Fig.11 c is a statistical chart of the degradation results of various materials in the Vis / PMS system. It can be seen that in the Vis / PMS system, ABF-5 material has the best degradation effect on CBZ. The CBZ degradation rate is 96.84% after 30 minutes of reaction. In this system, PMS can capture photogenerated electrons and inhibit the recombination of photogenerated carriers in the photocatalyst, thereby obtaining more electrons and holes to participate in the reaction and generate a large amount of active substances, thereby promoting the degradation of CBZ.

Claims

1. Application of a magnetic ternary photocatalyst in catalytic degradation of carbamazepine in water, characterized in that: The following steps are involved: S1. Add a magnetic photocatalyst to the water containing carbamazepine, stir thoroughly under light-proof conditions, then continue to add permonosulfate, and adjust the solution pH to 3-9; S2, placing the mixed solution under natural light for photocatalytic degradation; The method for preparing the magnetic ternary photocatalyst comprises the following steps: (1) Preparation of Fe3O4 magnetic particles; (2) dissolving Bi(NO3)3·5H2O in ethylene glycol, then adding AgNO3 solution thereto, stirring and reacting in the dark to obtain a mixed solution; (3) Add the Fe3O4 magnetic particles in step (1) to the mixed solution in step (2), stir thoroughly, then add KBr solution dropwise to the mixed system, place in a water bath for stirring and aging, then collect the precipitate and wash and dry it to obtain AgBr / BiOBr / Fe3O4 magnetic ternary photocatalyst.

2. The use according to claim 1, characterized in that In step (2) of the method for preparing the magnetic ternary photocatalyst, the concentration of Bi(NO3)3·5H2O in the mixed solution is 15-25 g / L, and the concentration of AgNO3 in the mixed solution is 0.5-2 g / L.

3. The use according to claim 1, characterized in that In step (3) of the method for preparing the magnetic ternary photocatalyst, the concentration of Fe3O4 magnetic particles in the mixed solution is 2-15wt%, and the concentration of KBr in the mixed system is 5-10g / L.

4. The use according to claim 1, characterized in that In step (3) of the method for preparing the magnetic ternary photocatalyst, the water bath temperature is 80-100° C., and the stirring aging time is 1-3 hours.

5. The use as claimed in claim 1, characterized in that The concentration of permonosulfate in the water in step S1 is 0.4-1.0 mM, and the concentration of the magnetic photocatalyst is 0.2-0.5 g / L.

6. The use as claimed in claim 1, characterized in that The peroxymonosulfate is potassium hydrogen persulfate.

7. The use as claimed in claim 1, characterized in that The photocatalytic degradation time is 1-30 minutes.

Citation Information

Patent Citations

  • Fe3O4 / BiOI / AgBr magnetic composite visible-light-driven photocatalyst and preparation thereof

    CN106513023A

  • Bismuth oxybromide ternary heterostructure photocatalyst as well as preparation method and application thereof

    CN109759122A

  • Microwave-synthesized oxygen vacancy BiOCl / Bi2S3 catalyst and preparation method thereof, and application of microwave-synthesized oxygen vacancy BiOCl / Bi2S3 catalyst

    CN110882705A